2021
DOI: 10.1017/s0022149x20001005
|View full text |Cite
|
Sign up to set email alerts
|

Redescription and molecular analysis ofPallisentis(Pallisentis)nandaiSarkar, 1953 (Acanthocephala: Quadrigyridae) in India

Abstract: Pallisentis (Pallisentis) nandai Sarkar, 1953 is a freshwater fish parasite restricted to the Indian subcontinent in the Ganga River and its tributaries. It was described from the leaffish, Nandus nandus (Hamilton) from the Ganga River delta at Calcutta. We recovered variant specimens from the same host species from the Ganga near its headwaters at Bijnor about 1500 km away. Our specimens were clearly identifiable as P. nandai but varied considerably from those in the original description, especially in the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Demidueterospinus , Brevitritospinus and Pallisentis based on the more consistent morphological characteristics like the difference in the size of the proboscis hooks from anterior to posterior circles, size of the cement gland and number of the giant nuclei of the cement gland. This sub-generic classification resolved the uncertainty related to the placement of different species within the genus contemporarily and was followed by Amin (2013) , Chaudhary et al (2019) , Gautam et al (2019) , Gautam et al (2020) , and Amin et al (2021) . Lately, the phylogenetic analyses based on the 18S gene marker by Chaudhary et al (2019) , Gautam et al (2020) and Rana and Kaur (2021) have shown monophyletic origin of the genus Pallisentis but create ambiguity within the genus.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Demidueterospinus , Brevitritospinus and Pallisentis based on the more consistent morphological characteristics like the difference in the size of the proboscis hooks from anterior to posterior circles, size of the cement gland and number of the giant nuclei of the cement gland. This sub-generic classification resolved the uncertainty related to the placement of different species within the genus contemporarily and was followed by Amin (2013) , Chaudhary et al (2019) , Gautam et al (2019) , Gautam et al (2020) , and Amin et al (2021) . Lately, the phylogenetic analyses based on the 18S gene marker by Chaudhary et al (2019) , Gautam et al (2020) and Rana and Kaur (2021) have shown monophyletic origin of the genus Pallisentis but create ambiguity within the genus.…”
Section: Discussionmentioning
confidence: 88%
“…The description of most of the Acanthocephalan species is lacking in complete morphological characterization which is based on few specimens and in addition the material cannot be referred due to the unavailability of the type specimens ( Amin et al, 2021 ). The species like P. channai Gupta et al, 2015 , Gupta et al, 2015 , P. vinodai Gupta et al (2015) and P. anandai Gautam et al (2017) were erected with incomplete morphological and molecular characterization and therefore are more likely to be questioned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other species in different genera of acanthocephalans with single-walled proboscis receptacle also have single long ventral PRS. Examples include Acanthogyrus (Acanthosentis) parareceptaclis Amin, 2005 (Quadrigyridae) from Japan (Amin 2005), Intraproboscis sanghae Amin, Heckmann, Sist et Basso, 2021 (Gigantorhynchidae) from Central Africa (Amin et al 2021a), Pallisentis (Pallisentis) nandai Sarkar, 1953 (Quadrigyridae) from India (Amin et al 2021b), and Tenuisentis niloticus (Meyer, 1932) (Tenuisentidae) from Burkina Faso (Amin et al 2016). In Acanthogyrus (Acanthosentis) fusiformis Amin, Chaudhary, Heckmann, Ha et Singh, 2019, there are two long similar PRS inserting at the posterior end of the receptacle (Amin et al 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…12). It was also prominent in whole hooks of Pallisentis nandai Sarkar, 1953 (see Amin et al , 2021) as well as in egg shells of Neoechinorhynchus qatarensis Amin, Saoud, Alkuwari, 2002 (see Heckmann et al , 2007). ‘The absence of sodium at the hook tip and its presence at the hook base and the opposite pattern of sulfur are characteristic of Neoechinorhynchus dimorphospinus Amin and Sey, 1996 hooks’ (Amin et al , 2019a, p. 616).…”
Section: Edxamentioning
confidence: 99%